Moving beyond gender: a systematic review of diversity data gaps in prospective trauma research - Stephanie Haering; Jule M. Kaeselau; Christine Knaevelsrud; Sinha Engel (European Journal of Psychotraumatology)
Background: To better understand heterogeneity in PTSD development and to ensure that knowledge of risk and intervention mechanisms is available for a diverse group of trauma exposed individuals, psychotraumatology needs to consider diversity in sample characteristics.Objective: In a comprehensive overview, we evaluated how nine diversity domains including age, socioeconomic status (SES), race/ethnicity, sexual orientation, care responsibilities, religion/worldview, mental health, physical health, and disability status were considered in prospective PTSD research. In in-depth analyses, we further investigated the assessment and representation of population groups with regard to age, SES and race/ethnicity.Method: Secondary analysis of a meta-analysis project that examined sex and gender considerations among k = 45 studies that prospectively assessed PTSD symptoms in trauma exposed individuals. In this study, additional information on diversity assessment and characteristics was systematically extracted and analysed.Results: While age was assessed in all studies, consideration of the remaining diversity domains was insufficient, ranging from 57.8% of studies for SES to 0.0% regarding sexual orientation and care responsibilities. The number of considered diversity domains did not increase over years. Our in-depth analyses showed that middle-aged, well-educated and racially non-marginalised individuals were overrepresented.Conclusions: Our study revealed diversity data gaps in reporting and representation, limiting the generalisability of research findings. Recommendations for increased diversity considerations are discussed.